Los hongos de colombia – viii some new species of soil fungi from colombia (1983)
Three new Colombian microfungi are described. Trichoderma inhamatum Veerkamp and amp; W. Gams and Rhinocladiella phaeophora Veerkamp and amp; W. Gams were isolated from a maizefield soil near Acacías, Dep. Meta, at 500 m alt.; Mortierella ornata W. Gams was isolated from a soil sample from mountain forest, Parque Nacional del Puracé, Cauca-Huila, at 3.100 m alt.